2006
DOI: 10.1093/nar/gkj460
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the human p21(waf1/cip1) gene promoter via multiple binding sites for p53 and the vitamin D3 receptor

Abstract: The main regulator of the human tumor suppresser gene p21(waf1/cip1) is the transcription factor p53, but more recently it has been suggested to be a primary anti-proliferative target for the nuclear receptor VDR in the presence of its ligand 1α,25-dihydroxyvitamin D3 (1α,25(OH)2D3). To identify VDR responding regions, we analyzed 20 overlapping regions covering the first 7.1 kb of the p21(waf1/cip1) promoter in MCF-7 human breast cancer cells using chromatin immuno-precipitation assays (ChIP) with antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 31 publications
10
188
0
1
Order By: Relevance
“…A fourth site (B, Fig. 1B) was reported at position -3,969 bp relative to the major TSS, 34 and a site at -11.7 kb from the major TSS (A, Fig. 1B) was identified and confirmed in the ChIP-PET study 23 and was later shown to regulate p53-dependent lincRNA-p21 transcription.…”
Section: Distinct P53 Genomic Binding Patterns In Normal and Cancer-dmentioning
confidence: 81%
“…A fourth site (B, Fig. 1B) was reported at position -3,969 bp relative to the major TSS, 34 and a site at -11.7 kb from the major TSS (A, Fig. 1B) was identified and confirmed in the ChIP-PET study 23 and was later shown to regulate p53-dependent lincRNA-p21 transcription.…”
Section: Distinct P53 Genomic Binding Patterns In Normal and Cancer-dmentioning
confidence: 81%
“…To evaluate regulation of p21 gene by p53 in senescent cells before and after DNA damage, the following primer pairs spanning À2478 to À2029 of p21 gene promoter were designed [24]; sense, 5 0 -CACCACTGAGCCTTCCTCAC-3 0 and anti-sense, 5 0 -CTGACTCCCAGCACACACTC-3 0 . Using the isolated chromatin templates, following PCR profile was applied: Preincubation for 5 min at 95°C, 34 cycles of 30 s at 95°C, 40 s at 54°C and 40 s at 72°C and one final incubation for 10 min at 72°C.…”
Section: Chip Assaymentioning
confidence: 99%
“…The common anti-proliferative VDR functions are associated with arrest at G 0 /G 1 of the cell cycle, coupled with up-regulation of a number of cell cycle inhibitors including p21 (waf1/cip1) and p27 (kip1) . Promoter characterization studies have demonstrated a series of vitamin D-responsive elements in the promoter-enhancer region of CDKN1A, a primary 1a,25(OH) 2 D 3 -responding gene (96,97) . By contrast, p27 (kip1) protein levels appear to be regulated by a range of post-transcriptional mechanisms, such as enhanced mRNA translation, and attenuating degradative mechanisms, often in a cell-type-specific manner (98)(99)(100) .…”
Section: Evidence Of Vitamin D Receptor Involvement In Cancermentioning
confidence: 99%